2018
DOI: 10.3390/molecules23081969
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Molecular Docking and Anticancer Activity of Diflunisal Derivatives as Cyclooxygenase Enzyme Inhibitors

Abstract: Cyclooxygenase enzymes play a vital role in inflammatory pathways in the human body. Apart from their relation with inflammation, the additional involvement of COX-2 enzyme with cancer activity was recently discovered. In some cancer types the level of COX-2 enzyme is increased indicating that this enzyme could be a suitable target for cancer therapy. Based on these findings, we have synthesized some new diflunisal thiosemicarbazides and 1,2,4-triazoles and tested them against androgen-independent prostate ade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…The reaction of hydrazide 45 with various aryl isothiocyanates afforded substituted hydrazinecarbothioamides 46a – f . Cyclization of compounds 46a – f to the corresponding triazole-3-thiones 47a – f occurred in basic media ( Scheme 11 ) [ 57 ]. The screening of compounds 47a – f against cancer cells revealed that compound 47f was found to be active against the colon carcinoma HCT-116 cancer cell line with a 6.2 μM IC 50 value.…”
Section: Synthesis Of 124-triazole-3-thionesmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of hydrazide 45 with various aryl isothiocyanates afforded substituted hydrazinecarbothioamides 46a – f . Cyclization of compounds 46a – f to the corresponding triazole-3-thiones 47a – f occurred in basic media ( Scheme 11 ) [ 57 ]. The screening of compounds 47a – f against cancer cells revealed that compound 47f was found to be active against the colon carcinoma HCT-116 cancer cell line with a 6.2 μM IC 50 value.…”
Section: Synthesis Of 124-triazole-3-thionesmentioning
confidence: 99%
“…The screening of compounds 47a – f against cancer cells revealed that compound 47f was found to be active against the colon carcinoma HCT-116 cancer cell line with a 6.2 μM IC 50 value. In addition, compounds 47e and 47f were found active against the human breast cancer T47D cancer cell line with IC 50 values of 43.4 and 27.3 μM, respectively [ 57 ].…”
Section: Synthesis Of 124-triazole-3-thionesmentioning
confidence: 99%
“…Thiosemicarbazides are very similar to thiosemicarbazones. A thiosemicarbazide skeleton is part of the structure of many compounds with interesting biological activities, including anticancer [ 10 , 11 , 12 , 13 ], antibacterial [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ], antifungal [ 19 ], and analgesic [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Anticancer activity and molecular modeling of NSAIDs derivatives have been studied and reported by Küçükgüzel and coworkers (Figure ).…”
Section: Introductionmentioning
confidence: 99%